Evaluating Sovereign Disaster Risk Finance Strategies : A Framework - Clarke, Daniel; Mahul, Olivier; Poulter, Richard; Teh, Tse Ling (World Bank, Washington, DC, 2016)
This paper proposes a framework for ex ante evaluation of sovereign disaster risk finance instruments available to governments for funding disaster losses. The framework can be used by governments to help choose between different financial instruments, or between different combinations of instruments, to achieve appropriate and financially efficient strategies to fund disaster losses, taking into account the risk of disasters, economic conditions, and political constraints. The paper discusses the framework in the context of a hypothetical country, with parameters selected to represent a disaster-prone small island state. The paper shows how a mix of instruments can be chosen to minimize the economic opportunity cost given the underlying disaster risk faced and prevailing economic and financial conditions.